Dźwiękowość jako czynnik budujący spójność serii gier wideo (na przykładzie serii Assassin’s Creed) - Bajew, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
In the article, the author raises the question of creating coherence in video game series by means of sound. In order to do this, he conducted research on four groups of SFXs (Sound Effects) extracted from the first seven games of the Assassin’s Creed series. It covered those SFXs that accompany the series’ signature gameplay moments. Sound samples recorded during gameplay were then analysed in the programme Reaper using Steinberg’s standard VST3 analysis tools. The research findings are compiled and presented in the form of a table. The author adopted the understanding of coherence outlined by Stanislav Gajda, and the concept refers to the mathematical formulation of the term.